Emplaced mobilities: Lisbon as a translocality in the migration journeys of Punjabi Sikhs to Europe - McGarrigle, Jennifer (2018)
The arrival in Portugal of recent migrants from the Indian subcontinent is normally a secondary movement from within Europe tied to the search for a regular pathway into legal integration in the EU. However, as favourable migration policy is not paired with easy economic integration onward migration is common. We argue that such complex migration strategies cannot be amply explored through an origin–destination model; instead we suggest that a translocal perspective provides a framework to examine connections and experiences of emplacement in places of passage/reception like Lisbon. Through a qualitative study of the migration journeys and emplaced practices of Punjabi migrants in Lisbon, our findings highlight relationality between multiple scales, elucidating how agency and structure interact at micro and macro levels in shaping migration experiences and outcomes. We show how the materiality of local community structures ensures the navigation of daily life in the city and provides pathways toward legality contributing to wider mobility regimes. Moreover, we illustrate how onward migration represents an individual strategy to realise different aspects of integration in other EU destinations challenging nation-statebound understandings of citizenship/settlement and integration.